PENGUATAN NILAI-NILAI ASWAJA DALAM KEHIDUPAN MASYARAKAT DI KUTO TANJUNG - Robby Jundi Lestari; Umar Dani; Rahmad Saleh (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
ABSTRACT The proliferation of religious ideologies with potential divisive effects has made the reinforcement of Ahlussunnah wal Jamaah (Aswaja) values increasingly crucial. This Community Engagement Program (PkM) aimed to strengthen the understanding and practice of Aswaja An-Nahdiyah in Kuto Tanjung Village, South Sumatra—a community that has long practiced NU traditions but has limited access to formal religious literacy. Using the Asset-Based Community Development (ABCD) method with participatory approaches (lectures, interactive discussions, and collective reflection), the program successfully internalized the four pillars of Aswaja—tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and i'tidal (justice)—as guidelines for daily life.The outcomes demonstrated that participants not only theoretically understood these principles but could also apply them to address challenges such as religious extremism and misinformation. In the long term, this initiative has solidified the existence of NU religious practices while enhancing community resilience based on Aswaja values to maintain social harmony. Keywords: Keywords: Strengthening Aswaja An-Nahdiyah, Religious Moderation, Community Resilience, Kuto Tanjung Village